TRADISI ZIARAH MAKAM PADA MASYARAKAT MELAYU DI DESA BINTAN BUYU KABUPATEN BINTAN - Desti, Rita Sintiya; Wahyuni, Sri; Elsera, Marisa (Universitas Tanjungpura, 2022)
This study aims to determine the significance of the grave pilgrimage tradition in Bintan Buyu Village, Bintan Regency. This study uses a qualitative research methodology with a descriptive approach with primary data sources, namely interviews with informants, caregivers, local communities, external communities, and traditional leaders, using targeted sampling. Data collection techniques were performed through observation, discussions, and documentation. Based on the results of this study, it can be seen that in the practice of the pilgrimage to the grave there are meanings in it, namely as a form of respect for ancestors, increasing community solidarity and strengthening values that exist in society such as religious values and the value of tranquility. The process of implementing the tomb pilgrimage tradition has 2 processes, namely the preparation process and the implementation process. In the tradition of the pilgrimage to graves, media such as pulut kuning, red eggs and yellow rice are used.